Field experimental study on optimal design of the rotary strip-till tools applied in rice-wheat rotation cropping system - Yang, Yanshan; Fielke, John; Ding, Qishuo; He, Ruiyin (International Journal of Agricultural and Biological Engineering, 2018)
The rice-wheat rotation system plays a significant role in Asian agriculture. The introduction of strip-tillage into the rice-wheat system for wheat planting offers a way to use conservation tillage practices to improve the seedbed quality, retain residue between rows and reduce energy input. A field experiment was conducted using an in-situ test rig. Three types of blade (bent C, straight and hoe) were evaluated in four tool configurations at four rotary speeds (180 r/min, 280 r/min, 380 r/min and 510 r/min) in a paddy soil. Furrow shape parameters, tillage-induced soil structures and energy consumption were assessed. Results showed that the straight blade configuration failed to create a continuous furrow at either 180 r/min or 510 r/min. The bent C blade configuration produced a uniform furrow profile but its furrow backfill was poor and unsuitable for seeding. The hoe blade configuration cut a continuous furrow and better tillage-induced soil structure, but it produced a much wider and non-uniform furrow shape. The mixed blade configuration (central hoe blades with two straight blades aside) provided a uniform furrow with good backfill and fine tilth by utilizing both the cutting effect of straight blades on the furrow boundaries and tensile fracturing of the furrow soil by the hoe blades. The torque of the mixed blade configuration was comparable with the bent C blade but was less than the hoe blades. Hence, a mixed blade configuration was recommended for rotary strip-tillage seeding using in rice-wheat system. Keywords: strip tillage, rotary strip-till tool, blade configuration, furrow quality, tilth, torque, rice-wheat rotation system DOI: 10.25165/j.ijabe.20181102.3347 Citation: Yang Y S, Fielke J, Ding Q S, He R Y. Field experimental study on optimal design of the rotary strip-till tools applied in rice-wheat rotation cropping system. Int J Agric & Biol Eng, 2018; 11(2): 88–94.